(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2020)
This study aims to analyse modal phrases in the European Commission’s Serbia 2019 report and to draw conclusions about modality in political writing in general. 560 phrases with modal meaning were identified in the report. The most frequent are modal verbs need and should and adverbs still and yet. The verb following the modal form is usually in passive. Almost all the modals belong to the category of priority modality, most commonly deontic. All priority modals analysed are directives, specifically obligatives. All priority modal verbs were used subjectively. The study concludes that political writing in general is of modal nature.